Compressible Electrodes: 3D‐Printed, Superelastic Polypyrrole–Graphene Electrodes with Ultrahigh Areal Capacitance for Electrochemical Energy Storage (Adv. Mater. Technol. 7/2018). Issue 7 (12th July 2018) - Qi, Zhen; Ye, Jianchao; Chen, Wen; Biener, Juergen; Duoss, Eric B.; Spadaccini, Christopher M.; Worsley, Marcus A.; Zhu, Cheng
Abstract : In article number1800053, graphene‐polypyrrole composites with three‐dimensional digitally designed architectures were demonstrated by Cheng Zhu and co‐workers via chemical deposition of polypyrrole thin‐films onto 3D printed graphene aerogels. Taking advantage of the 3D digital designed architectures, the areal capacitance was greatly enhanced, thus allowing full utilization of the limited footprints of microdevices. The compressibility of the composites originates from the graphene aerogel backbones.